2005
DOI: 10.1159/000088365
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effect of Prostaglandin E<sub>2</sub> in a Rat Model of Esophagitis Mediated by EP1 Receptors: Relation to Pepsin Secretion

Abstract: We investigated the roles of prostaglandin (PG) E2 and cyclooxygenase (COX) isoenzymes in the mucosal defense of the esophagus, using subtype-selective EP agonists and antagonists as well as various COX inhibitors, in an acute rat esophagitis model. The animals were used after fasting for 18 h. Acid reflux esophagitis was induced by ligating both the pylorus and the transitional region between the forestomach and the glandular portion under ether anesthesia, and the damage was examined 3 or 4 h late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…These biphasic effects were mimicked by 17-phenyl PGE 2 and significantly antagonized by the EP1 antagonist ONO-8711, while other PGE derivatives, including EP2, EP3, and EP4 agonists, had no effect. PGE 2 and 17-phenyl PGE 2 had no effect on acid secretion but significantly increased pepsin secretion, in an EP1 antagonist-sensitive manner (16). These results indicate that PGE 2 has a biphasic effect on acid reflux esophagitis depending on the dose: a protective effect at lower doses and an aggravating effect at high doses, both mediated by EP1 receptors.…”
Section: Esophageal Protectionmentioning
confidence: 75%
“…These biphasic effects were mimicked by 17-phenyl PGE 2 and significantly antagonized by the EP1 antagonist ONO-8711, while other PGE derivatives, including EP2, EP3, and EP4 agonists, had no effect. PGE 2 and 17-phenyl PGE 2 had no effect on acid secretion but significantly increased pepsin secretion, in an EP1 antagonist-sensitive manner (16). These results indicate that PGE 2 has a biphasic effect on acid reflux esophagitis depending on the dose: a protective effect at lower doses and an aggravating effect at high doses, both mediated by EP1 receptors.…”
Section: Esophageal Protectionmentioning
confidence: 75%
“…BPC 157-reduction of acute alcohol-, indomethacin-, aspirin-lesions (5 -7, 29, 30, 38), or chronic alcohol drinking-(31), acetic acid- (16,43) lesions is likely relevant for its effect on endogenous prostaglandin (PG) in esophagitis and chronic esophagitis attenuation. Indeed, it was recently reported that the acid reflux esophagitis was prevented or aggravated by prior administration of PGE 2 or indomethacin, respectively (44). However, various PGs differently affect lower esophageal sphincter, pyloric sphincter, and ileocaecal sphincter, while pyloric sphincter is not responsive to PGs treatment (45).…”
Section: Discussionmentioning
confidence: 99%
“…EP 1 receptors are essential for HCO 3 Ϫ secretion in response to mucosal acidification in the stomach . A dual role for EP 1 receptors in esophagitis is clearer, whereby PGE 2 has a protective effect at low doses and a deleterious effect at high doses (Yamato et al, 2005). In the kidney, PGE 2 activates EP 1 receptors to inhibit Na ϩ absorption by the renal collecting duct (Guan et al, 1998).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%